Role of Ayurveda Modalities to Manage Medoroga (Dyslipidemia) – A Review Article - Shahu, Komal; Singh, Naimish Raj; Varsakiya, Jitendrakumar Nathabhai (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Dyslipidemia, a major lifestyle disorder, is characterized by abnormal lipid metabolism, increasing the risk of cardiovascular diseases, diabetes, and stroke. Ayurveda correlates dyslipidemia with Medoroga, primarily caused by Kapha Dosha and Meda Dhatu vitiation. It is classified as Abaddha Meda, referring to free-circulating fat in the blood, resembling modern lipid abnormalities. Aim and Objective: To review Medoroga in the context of dyslipidemia, analyzing its etiopathogenesis and management from an Ayurvedic perspective. Materials and Methods: A comprehensive review of Ayurvedic classical texts, modern medical literature, and research articles from sources such as Google Scholar, PubMed, and ResearchGate. Discussion: Dyslipidemia is caused by genetic (Beejdosha) and environmental factors, including a sedentary lifestyle, poor diet, and metabolic disturbances. Ayurveda attributes it to impaired Agni, leading to Ama formation, Srotorodha (obstruction of microchannels), and excessive Meda accumulation. Beejdosha predisposes individuals to lipid metabolism disorders, leading to hereditary dyslipidemia. Ayurvedic management includes Nidana Parivarjana (avoidance of causative factors), Samshodhana (purification therapies), Samshamana (palliative treatment), Pathya– Apathya (diet and lifestyle modifications), and Holistic interventions: Yoga, meditation, and stress management contribute to overall metabolic balance. Conclusion: Ayurveda provides a holistic approach to dyslipidemia by addressing both lipid imbalances and metabolic dysfunctions. Integrating Ayurvedic principles with modern research can enhance dyslipidemia management and prevent associated complications.